2020
DOI: 10.18502/kss.v4i1.6007
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Aspects of Financial – Banking Responsibility

Abstract: We all as individuals have responsibility for any decisions, in terms of time, value and risk. In time, the system in which we are evolving requires different behaviors that are in alignment with our interests, as individuals, as organizations or as institutions. The paper brings into attention the concept of financial responsibility manifested in financial – banking environment, as a concept and as a species of financial education (or literacy). The main aim of this article is to evaluate the awareness, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…This paper identifies the root cause of loan and loan repayment syncope in a low level of financial literacy. The results of this paper resonate with other previous studies that support and reinforce the idea that the level of financial literacy is low due to a low level of financial responsibility [20]. Thus, the research conducted revealed such aspects as lack of general financial and economic knowledge, reluctance to access new banking products (traditional ones occupying the primary place in use), susceptibility in the clientemployee-bank relationship, little confidence in the information communicated by the financial institution, the need to seek financial advice, the need for minimum financial and easy to access training options, etc.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This paper identifies the root cause of loan and loan repayment syncope in a low level of financial literacy. The results of this paper resonate with other previous studies that support and reinforce the idea that the level of financial literacy is low due to a low level of financial responsibility [20]. Thus, the research conducted revealed such aspects as lack of general financial and economic knowledge, reluctance to access new banking products (traditional ones occupying the primary place in use), susceptibility in the clientemployee-bank relationship, little confidence in the information communicated by the financial institution, the need to seek financial advice, the need for minimum financial and easy to access training options, etc.…”
Section: Discussionsupporting
confidence: 91%
“…Actions to achieve the sustainable development goals of society can be implemented through the active involvement of financial institutions not only in lending but also in the transmission of knowledge on minimum financial education so that partnership relations with consumers are beneficial to both parties. Therefore, there is the question of the financial responsibility of banking institutions with an imprint on the well-being of the person and the impact on the development of the economy [20]. The study conducted by Renate Doina Bratu helps establish the awareness, manifestation, and evaluation of the importance of financial responsibility in Romania by focusing on population's savings behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Within the existing scientific literature, reference is also often made to financial education and the need for its constant improvement, under the influence of numerous factors, among which the digital evolution can be mentioned. As per Bratu [6], financial education contributes to increasing the capacity of individuals to use complex financial services and products. The same study notes the fact that, in order to use modern, intensively developed financial products, financial education must be constantly developed, with an emphasis on self-education using technology.…”
Section: Introductionmentioning
confidence: 99%